Tree diversity and regeneration status in the different forest types of Kotla watershed (Uttarkashi, Uttarakhand, India) - Rana, Krishan Pal Singh Rana; Koshal, Avadhesh Kumar Koshal; Bajpai, Atal Bihari Bajpai (Ecological Questions, 2022)
The present study aimed to assess the diversity and regeneration status of tree species in different forest types viz., Pinus forest (PF), Pinus-Oak mixed forest (POF) and Deodar forest (DF) of Kotla watershed (Barkot, Uttarkashi, Uttarakhand). The data were collected through quadrat method and analyzed quantitatively. A total of 28 tree species, belonging to 21 families were recorded in the sampling area (3 forests 10 plots in each plot size 400 m2). Fagaceae, Pinaceae, Ericaceae, Fabaceae and Juglandaceae were the major families (in terms of number of species). The species-area curves (SACs) of PF and DF reached an asymptote while it predicted more species (din not reach asymptote) in case of POF. The resulted values of different diversity indices (i.e., Dominance, Simpson, Shannon, Evenness, Margalef, and Equitability) revealed that the POF was most diverse (in tree diversity) followed by PF and DF. The ranked species abundance (RSA) curve of POF was log normal type but geometric series type for PF and DF. The density-diameter curves (d-d curves) was reverse J-shaped for POF while in case of PF and DF, the higher densities were observed for middle DBH classes in comparison to lowest and highest DBH classes. The overall regeneration status of the forests in the area was fair (25.8% tree, 18.6% saplings and 55.6% seedlings). The present study provides a deeper understanding of tree diversity pattern and regeneration status from a pocket of Indian Himalayan Region (IHR).